PSYCHOLOGICAL FEATURES OF GENDER DIFFERENTATION IN EMOTIONAL EXPERIENCE - Siddikova Barno (Bright Mind Publishing, 2025)
This article explores individual differences and gender-specific characteristics in emotional experiences and expressions. It highlights how emotional intensity, stability, and reactivity vary between individuals, emphasizing the influence of both biological factors—such as nervous system functioning—and environmental factors, including upbringing and social expectations.
Keywords: Emotional experiences, gender differences, emotional expressiveness, emotional reactivity, emotional intelligence, nervous system, social norms, emotional regulation.